Association between polysomnography-measured sleep parameters and cognitive impairment in elderly patients with depression - Zhou, Jiaojiao; Que, Jianyu; Wang, Yida; Ren, Li; Zhang, Saina; Ma, Xianglin; Fan, Yintai; Zhang, Qing’e; Chen, Xueyan (Frontiers in Psychiatry, 2025)
ObjectiveLimited research has explored the associations between sleep disturbances (SD) and cognitive impairment (CI) in elderly patients with depression, particularly by incorporating polysomnography (PSG) to assess sleep quality. This study was conducted to determine correlations between PSG-quantified sleep parameters and CI among individuals with late-life depression.Methods65 elderly patients with depression were included in the study. The sleep status was assessed using PSG, while cognitive function was evaluated using the Mini-Mental State Examination (MMSE). The correlation between PSG-measured sleep parameters and cognitive function was analyzed.ResultsCI was observed in 31 (47.7%) individuals. Depressed elderly patients with CI exhibited a shorter total sleep time (TST) compared to those without CI. Furthermore, their sleep efficiency (SE) was reduced as evidenced by shortened durations and proportions of N1 and N3. Conversely, the proportion of non-rapid eye movement (NREM) and N2 increased in this group. Additionally, both the duration and proportion of rapid eye movement (REM) were decreased. Spearman correlation analysis revealed a linear relationship between the MMSE score and various sleep parameters. However, in the multiple linear regression model, only the proportions of NREM exhibited a significant linear relationship with the MMSE scores.ConclusionsIn elderly patients with depression, a significant linear relationship was observed between the MMSE score and various sleep parameters measured by PSG.